2022
DOI: 10.1002/jbm.b.35055
|View full text |Cite
|
Sign up to set email alerts
|

Custom design and biomechanical clinical trials of 3D‐printed polyether ether ketone femoral shaft prosthesis

Abstract: During the surgical resection and reconstruction of a pathological femoral fracture, the removal of the femoral tumor leaves a large bone defect. Thus, it is necessary to reconstruct the defect and perform internal fixation. Polyether ether ketone (PEEK) has been widely used in spinal fusion and cranioplasty given its excellent biomechanical properties, biocompatibility, and stability. The typical design method of femoral prosthesis is based on the contralateral mirror image model (M-model), and we propose a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Besides, studies have demonstrated that when applying a vertical load to simulate the early postoperative internal fixation load-bearing, the stress is mainly concentrated in the middle of the IM nail (Chen et al, 2018;Wang et al, 2020). Wu et al (2022) applied the 3D printed polyether ether ketone prosthesis to repair the femoral shaft defect and observed middle-concentrated stress of the IM nail. As shown by the FEA results in the present study, when the interlocking IM nail was applied to stabilize prostheses for metaphyseal bone defects, the stress was mainly distributed along the IM nail (the maximum stress concentration occurred at the middle of the nail) (Figure 4), which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, studies have demonstrated that when applying a vertical load to simulate the early postoperative internal fixation load-bearing, the stress is mainly concentrated in the middle of the IM nail (Chen et al, 2018;Wang et al, 2020). Wu et al (2022) applied the 3D printed polyether ether ketone prosthesis to repair the femoral shaft defect and observed middle-concentrated stress of the IM nail. As shown by the FEA results in the present study, when the interlocking IM nail was applied to stabilize prostheses for metaphyseal bone defects, the stress was mainly distributed along the IM nail (the maximum stress concentration occurred at the middle of the nail) (Figure 4), which is consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the addition of the lateral wing did not significantly affect the stress concentration characteristics of the IM nail when by comparing Mode I and Mode IV. In a previous study, Wu et al applied a 3D printed polyether ether ketone prosthesis to repair the femoral shaft defect and observed that the stress was concentrated in the middle ( 23 ). Similarly, when an IM is used to fix long bone fractures, the stress can also be effectively transmitted and concentrated mainly in the middle region of the IM nail, which could help increase the mechanical stability and reduce stress shielding ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…FEA has been applied to evaluate and compare the biomechanical characteristics in prosthesis design and stem fixation (E,F,G) ( 17 19 ).In terms of the design of 3D printed prostheses, FEA has also been applied to analyze biomechanical performance and stress distribution ( 20 22 ), and predict the bone-implant interface stress. Wu et al applied FEA to compare the differences in the mechanical properties of two prosthesis model and successfully designed a 3D printed polyether ether ketone femoral shaft prosthesis for repairing critical bone defects ( 23 ). These results have laid a foundation for the development of this study.…”
Section: Introductionmentioning
confidence: 99%
“…These works have investigated the range of 3D printing from electron-beam printing of titaniumbased spinal cages 91 to 3D printing of Hydroxyapatite and/or polymeric hydrogel biomaterials. Three-dimensional printing of gelatinbased hydrogels 92,93 for bone and cartilage applications was reported as were printed PEEK hip stems 94 and hydroxyapatite-based biomaterials. 95 Many other topics were covered in JBMR B in the past year and no review can possibly cover all that was accomplished.…”
Section: Biomaterials Research In Advanced Materials (Ekaterina Peret...mentioning
confidence: 99%